A perspective on experimental findings and theoretical explanations of novel dynamics at free surface and in freestanding thin films of polystyrene. Issue 7 (23rd March 2016) - Ngai, Kia L.; Prevosto, Daniele; Capaccioli, Simone
Abstract : Most studies of the dynamics at the surface and in thin films of polystyrene (PS) are focused on the change of glass transition temperature from the bulk value. In this perspective, we highlight three new developments in research on the dynamics of PS in high molecular weight (MW) freestanding PS thin films and at the surface of low MW PS. Novel findings from these developments require consideration of viscoelastic mechanisms with length scales longer than the segmental α -relaxation. The first development is the creep compliance measurements of high-MW PS thin films, probing not only the segmental α -relaxation, but also the polymer chain modes at higher compliance levels, including the sub-Rouse modes and the Rouse modes. The compliance data indicate the relaxation times of the sub-Rouse modes are reduced in thinner films like that of the segmental α -relaxation but to a much less extent. The second development is the novel observation of two glass transitions in freestanding polystyrene thin films by ellipsometry. The upper and lower glass transitions occurs, respectively, at temperatures and, both are below the bulk glass transition temperature. While the lower transition at is associated with the segmental α -relaxation, the only viable explanation of the origin of the upper transition at is from another intrinsic viscoelastic mechanism of PS, and not at different location of the film. Supported by various experiments on PS and other polymers, we show that the sub-Rouse modes are cooperative and coupled to density, and hence giving rise to the upper glass transition in freestanding PS films. The sub-Rouse relaxation times will increase on physical ageing, and bring along an increase in density of the freestanding film due to the coupling. This prediction can be checked by performing ageing experiment. The third development is the reduction of viscosity at the free surface of low MW PS. Since viscous flow of low MW PS is definitely carried out by the sub-Rouse modes and not by the segmental α -relaxation, the experimental finding is direct evidence of enhancement of mobility of the sub-Rouse modes by the mitigation of intermolecular coupling at the surface, consistent with the explanations given for the findings in the two other developments. The enhancement of mobility of the sub-Rouse modes occurs simultaneously with the same effect on the segmental α -relaxation. Notwithstanding, at the surface, the observed reduction of viscosity from the sub-Rouse modes is significantly smaller than the reduction of the segmental relaxation time, which is explained semiquantitatively. Altogether, the three recent advances in the study of dynamics of polymer thin films and at the free surface have shown not only the change of the glass transition temperature effected by the segmental α -relaxation is interesting, but also that of the sub-Rouse modes.